2014
DOI: 10.18388/abp.2014_1913
|View full text |Cite
|
Sign up to set email alerts
|

The pH optimum of native uracil-DNA glycosylase of Archaeoglobus fulgidus compared to recombinant enzyme indicates adaption to cytosolic pH.

Abstract: Uracil-DNA glycosylase of Archaeoglobus fulgidus (Afung) in cell extracts exhibited maximal activity around pH 6.2 as compared to pH 4.8 for the purified recombinant enzyme expressed in Escherichia coli. Native Afung thus seems to be adapted to the intracellular pH of A. fulgidus, determined to be 7.0±0.1. Both recombinant and native Afung exhibited a broad temperature optimum for activity around 80°C, reflecting the A. fulgidus optimal growth temperature of 83°C. Adaption to the neutral conditions in the A. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…fulgidus UDG has the optimal temperature of the enzyme activity at 80 o C (20). In this work, we demonstrated that Tba UDG194 has maximum cleavage efficiencies at >85 o C, which is close to optimal growth temperature of its host.…”
Section: Discussionsupporting
confidence: 54%
“…fulgidus UDG has the optimal temperature of the enzyme activity at 80 o C (20). In this work, we demonstrated that Tba UDG194 has maximum cleavage efficiencies at >85 o C, which is close to optimal growth temperature of its host.…”
Section: Discussionsupporting
confidence: 54%